2010
DOI: 10.4137/bci.s4210
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Racemization and Deposition in the Lungs of Aged Rats

Abstract: Isomerization of amino acids in proteins has recently been identified as a part of the aging process. Increases in d-amino acids as a consequence of isomerization influence the function and structure of proteins. Senescence-related pulmonary diseases, such as chronic obstructive pulmonary disease, are thought to be caused by reductions of lung function with age. We hypothesized that changes of protein structure in lung tissue induced by the isomerization of amino acids could result in decreased lung function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…There is a need for reliable techniques to screen for DNA preservation prior to destructive sampling. An increase in amino acid racemization has been linked with age, and aspartic acid racemization has been successful in forensic age estimation when the postmortem interval is relatively short. , The extent of aspartic acid racemization (AAR) was thought to be a good measure of the likelihood of DNA survival, but Collins et al found no correlation between the extent of AAR and DNA amplification success and conclude that amino acid racemization is not a useful screening technique for ancient DNA from bone …”
Section: Discussionmentioning
confidence: 99%
“…There is a need for reliable techniques to screen for DNA preservation prior to destructive sampling. An increase in amino acid racemization has been linked with age, and aspartic acid racemization has been successful in forensic age estimation when the postmortem interval is relatively short. , The extent of aspartic acid racemization (AAR) was thought to be a good measure of the likelihood of DNA survival, but Collins et al found no correlation between the extent of AAR and DNA amplification success and conclude that amino acid racemization is not a useful screening technique for ancient DNA from bone …”
Section: Discussionmentioning
confidence: 99%
“…Another part of PTMs Sp is known to disrupt the natural course of molecular events, often leading to pathogenic misfolding, malfunction, and aggregation of proteins. One of the most studied forms of pathogenic reactions is racemization [ 69 , 70 ]. As an unavoidable consequence of pathogenic PTMs, we can expect that even small (limited only to one or two AAs) racemization can trigger the deviation from the NS.…”
Section: Biological Language Of Protein Conformationmentioning
confidence: 99%
“…d-Ser is known to be involved in glutamate transmission and plays a role in long-term potentiation [ 378 ]. D-AAs found in many AD-related proteins including neuronal-specific neurofilament-L [ 379 ], MBP [ 56 ], and in protein phosphatase PPC1 [ 380 , 381 ]. PPC1 and PPC2 are involved in TAU de-phosphorylation at multiple serine/threonine sites [ 382 , 383 ].…”
Section: Racemization Role At Molecular Cellular and System (Organ) Levelsmentioning
confidence: 99%